A prospective comparison of the operative outcome of D1 and modified D2 gastrectomy in adenocarcinoma of the stomach - Tusar Kanti Saradar; Jorge Pal; Gautam Ghosh; Bikash Chandra Ghosh (Asian Journal of Medical Sciences, 2022)
Background: Gastric adenocarcinoma is a leading cause of cancer and cancer related death among Asian countries. Although there is considerable improvement in chemoradiation, surgery still remains the primary curative modality with special emphasis on lymphadenectomy.